A study to evaluate the effectiveness of a total back care programme for group rehabilitation of selected patients with chronic low back pain - Bardin, Lynn Diane (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScPhysio)--Stellenbosch University, 1998.